Penyelesaian Persamaan Linear-Non Linear Dan Persamaan Differensial Dengan Metode Kesamaan - Abraham Salusu (Jurnal Keguruan dan Ilmu Pendidikan, 2017)
The solution of an equation either in the form of linear, non linear, or differential equation can be done by using formulas or rules for all those equations. Equality method is a simple form of linear, non linear, and differential equation since this method does not need so much knowledge of theorem of those equations. Equality method only places a form of equation in an original form where the sum has to be the same and fixed always.